Cerebral magnetic resonance elastography in supranuclear palsy and idiopathic Parkinson's disease - Lipp, Axel; Trbojevic, Radmila; Paul, Friedemann; Fehlner, Andreas; Hirsch, Sebastian; Scheel, Michael; Noack, Cornelia; Braun, Juergen; Sack, Ingolf (NeuroImage: Clinical, 2013)
Detection and discrimination of neurodegenerative Parkinson syndromes are challenging clinical tasks and the use of standard T1- and T 2-weighted cerebral magnetic resonance (MR) imaging is limited to exclude symptomatic Parkinsonism. We used a quantitative structural MR-based technique, MR-elastography (MRE), to assess viscoelastic properties of the brain, providing insights into altered tissue architecture in neurodegenerative diseases on a macroscopic level. We measured single-slice multifrequency MRE (MMRE) and three-dimensional MRE (3DMRE) in two neurodegenerative disorders with overlapping clinical presentation but different neuropathology - progressive supranuclear palsy (PSP: N = 16) and idiopathic Parkinson's disease (PD: N = 18) as well as in controls (N = 18). In PSP, both MMRE (Δμ = - 28.8%, Δα = - 4.9%) and 3DMRE (Δ|G*|: - 10.6%, Δφ: - 34.6%) were significantly reduced compared to controls, with a pronounced reduction within the lentiform nucleus (Δμ = - 34.6%, Δα = - 8.1%; Δ|G*|: - 7.8%, Δφ: - 44.8%). MRE in PD showed a comparable pattern, but overall reduction in brain elasticity was less severe reaching significance only in the lentiform nucleus (Δμ n.s., Δα = - 7.4%; Δ|G*|: - 6.9%, Δφ: n.s.). Beyond that, patients showed a close negative correlation between MRE constants and clinical severity. Our data indicate that brain viscoelasticity in PSP and PD is differently affected by the underlying neurodegeneration; whereas in PSP all MRE constants are reduced and changes in brain softness (reduced μ and |G*|) predominate those of viscosity (α and φ) in PD. © 2013 The Authors.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Elasticity; MR-elastography; MRE; Parkinson disease; Progressive supranuclear palsy; Viscosity